Clinical outcomes of percutaneous mitral valve repair with MitraClip for the management of functional mitral regurgitation. Issue 6 (1st April 2019) - Marmagkiolis, Konstantinos; Hakeem, Abdul; Ebersole, Douglas G.; Iliescu, Cezar; Ates, Ismail; Cilingiroglu, Mehmet
Abstract: Objectives: To evaluate the safety and efficacy of percutaneous mitral valve repair for the management of functional mitral insufficiency. Background: Severe FMR is present in 25–30% of patients with heart failure and is an independent predictor of mortality and hospitalizations in patients with both ischemic and nonischemic cardiomyopathy. MitraClip therapy has been approved for high surgical risk patients with primary mitral regurgitation. Recent studies including two randomized trials have yielded conflicting results in terms of its clinical efficacy and outcomes for FMR. A quantitative evaluation and synthesis of this information are essential in elucidating the role of MitraClip repair for FMR. Methods: We performed a literature search using PubMed, EMBASE, and Cochrane Central Register of Controlled Trials from September 2008 to September 2018. Studies comparing percutaneous mitral valve repair using the MitraClip device against conservative therapy for the management of functional mitral regurgitation were included. Results: Seven studies with 1, 174 patients in MitraClip group and 1, 015 patients in medical therapy group met inclusion criteria. The 12‐month mortality in the MitraClip group was 18.4% compared with 25.9% in the medical therapy group (odds ratio [OR]: 0.65 [0.50, 0.86]; p < .002). The rate of readmission at 12 months was 29.9% in the MitraClip group compared with 54.1% in the medical therapy group (OR: 040 [0.32–0.49]; p < .0001. The prognostic efficacy of MitraClip repair appears to be more substantial over longer follow‐up period over medical therapy alone. Conclusions: Based on the results of this meta‐analysis, percutaneous mitral valve repair with MitraClip appears to be superior to medical therapy for symptomatic moderate‐to‐severe functional mitral insufficiency. Further clinical research is needed to identify the ideal patient subgroups who receive maximum benefit with the MitraClip therapy.